PENGARUH JUMLAH PENDUDUK, PDRB, INFLASI DAN JUMLAH WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2014-2016 - Wahyu Candra, 14.05.52.0262; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the effect of Population, GRDP, Inflation and Number of Tourists on Regional Original Revenue in Districts / Cities in Central Java Province in 2014-2016. The population in this study were all districts and cities in Central Java Province. The sample of this study was 35 Regencies and Cities in Central Java Province with the period 2014-2016. This study uses secondary data obtained from BPS Central Java Province. The analytical method used in this study is multiple linear regression. Based on the results of the study it can be concluded that the Number of Tourists has a significant positive effect on Regional Original Income and Inflation has a significant negative effect on Regional Original Income. While the Number of Population has a positive and insignificant effect on Regional Original Income and GRDP has no significant negative effect on Regional Original Revenue.